(untitled) (Mongolian Journal of International Affairs, 2025)
This study examines the complex relationships between economic factors and conflict-related variables in 19 conflict-affected countries (e.g., Afghanistan, Colombia, Democratic Republic of the Congo, Sudan, and Yemen) from 2000 to 2023. Using data from the World Bank, we analyze the interactions between foreign direct investment (FDI), GDP per capita growth, internally displaced persons (IDPs), military expenditures, and combat-related fatalities. The results suggest that FDI has a moderately positive effect on GDP growth, especially in countries with stable governance and institutional frameworks (e.g., Israel, Colombia). However, persistent instability and governance challenges (e.g., Iraq, DRC) significantly deter FDI inflows and undermine growth prospects. The negative correlation between IDPs and GDP growth highlights the economic costs of displacement, driven by human capital losses, labor market disruptions, and resource strains, as evidenced in Sudan and the DRC. Military spending, while associated with reductions in IDPs and combat deaths, shows no significant direct effect on GDP growth, suggesting that the opportunity costs of defense spending may hinder long-term economic development in conflict-prone regions. The strong correlation between combat deaths and IDPs perpetuates cycles of violence and displacement, contributing to economic stagnation, as observed in Ethiopia and Afghanistan. Regression analysis identifies FDI as a key predictor of growth, although its impact is moderated by contextual factors such as governance quality and infrastructure development (with a low R² of 0.290, indicating the influence of other unexamined variables). These findings highlight the heterogeneous impact of conflict on economic development and underscore the need for context-specific policy interventions that focus on governance reforms, human capital recovery, and conflict prevention to break the cycle of violence and underdevelopment.